The Educational Leadership of the School Principal in Enhancing Learning Quality through Teacher Interaction and Classroom Climate at Muhammadiyah Special Program Elementary School, Banyudono - Nuruddin; Sukari (At Turots: Jurnal Pendidikan Islam, 2026)
This study aims to examine the role of the principal’s educational leadership in improving learning quality through teacher interaction and classroom climate at Muhammadiyah Special Program Elementary School, Banyudono. The research employed a quantitative descriptive approach to analyze how educational leadership practices influence instructional processes and classroom conditions. The population of this study consisted of students at the school, with a sample of 30 students selected using a purposive sampling technique. Data were collected through questionnaires, classroom observations, and documentation, and were analyzed using descriptive statistical techniques in the form of percentages. The results indicate that the principal’s educational leadership was implemented at a high level, with an achievement percentage of 85.4%, indicating strong leadership effectiveness. Teacher interaction in the learning process reached a percentage of 82.7%, categorized as good, reflecting active and constructive communication between teachers and students. Meanwhile, the classroom climate achieved a percentage of 84.1%, indicating a conducive and supportive learning environment. Overall, the quality of learning showed a positive outcome with an average percentage of 83.9%, suggesting that educational leadership, teacher interaction, and classroom climate significantly contribute to the enhancement of learning quality. These findings conclude that effective educational leadership by the school principal plays a crucial role in fostering positive teacher interaction and a conducive classroom climate, which in turn improves the overall quality of learning at the elementary school level